ESTIMATION OF HETEROSIS FOR GRAIN YIELD, ITS COMPONENTS AND GRAIN QUALITY TRAITS IN HYBRID RICE (Oryza sativa L.) - A.S. HARI PRASAD, K. PARIMALA, CH. SURENDER RAJU and (The Journal of Research, PJTSAU, 2019)
The present investigation was carried out to study the magnitude of heterosis in yield components and grain quality traits of 27 rice hybrids developed by crossing three male sterile lines with seven restorers in line x tester design. The hybrids IR-80555A x RNR-17462 and IR-80555A x RNR-15028 showed desirable negative heterobeltiosis and standard heterosis for days to 50% flowering. The hybrids, IR-80555A x RNR-2458, IR-80555A x RNR-17462 and IR-79156A x RNR-2458 exhibited highly significant negative standard heterosis for plant height. Twenty hybrids were found to be significantly superior over the check for number of filled grains per panicle. The hybrids IR-80555A x RNR-15028 (33.35%), IR-68897A x RNR-2781 (26.13%) and IR-68897A x RNR17462 (25.87%) showed highest significant positive heterosis over standard check for grain yield per plant. For the trait head rice recovery, 21 hybrids were found to be superior over the check within the range of 8.67 to 23.04 per cent. Highest positive standard heterosis was recorded by the hybrid IR-79156A x WGL-3962 (23.77%) for kernel length. The range of heterobeltiosis varied from -26.54 to 31.53 per cent for kernel L/B ratio. The hybrids, IR-79156A x RNR-15038 (25.40%) IR-68897A x RNR-15038 (24.33%) were found to be good for kernel length after cooking which expressed highest positive significant standard heterosis. The hybrids IR-68897A x RNR-17462, IR-68897A x WGL-3962, IR-80555A x RNR-2781 and IR-79156A x RNR-15038 were found to be good for yield contributing traits such as productive tillers per plant, number of filled grains per panicle, spikelet fertility (%), grain yield per plant, kernel length after cooking and kernel elongation ratio. The hybrid IR-79156A x RNR-15038, showed superiority for both yield components and quality traits.